Aberration corrections of doughnut beam by adaptive optics in the turbid medium. Issue 11 (28th July 2019) - Wu, Chenxue; Chen, Jiajia; Si, Ke; Song, Yanchun; Zhu, Xinpei; Hu, Lejia; Zheng, Yao; Gong, Wei
Abstract: The doughnut beam is a spatially structured beam which has been widely used in super‐resolution microscopy, laser trapping and so on. However, when it passes through thick scattering medium, aberrations will seriously affect its performance. Currently, adaptive optics (AO) has become one of the most powerful tools to compensate aberrations. However, conventional AO always suffers from limited corrected field of view (FOV). Here, we propose a method with conjugate AO system based on coherent optical adaptive technique. The results show that the corrected FOV can be improved effectively. For a wide range of the optical applications with doughnut beam, our method has potentials in correcting aberrations with high speed in turbid media.(A) Mouse brain slice, (B) the distribution of r PAO, (C) the distribution of r CAO . The vortex beam focus of the blue point in (B) and (C) among a 137.5 × 137.5 μm FOV (D1) ideally, (D2) with scattering, (D3) in pupil AO system and (D4) in conjugate AO system. Abstract : The aberrations of doughnut beam in a turbid medium are corrected in conjugate adaptive optics (AO) system based on coherent optical adaptive technique. It is proved that conjugate AO system works well both on recovering doughnut beam and Gaussian beam. For mouse brain tissue, the area of corrected field of view of conjugate AO system is 4.69 times that of pupil AO, which shows potentials in high speed biological imaging.